Penerapan Metode Elimination and Choice Expressing Reality Untuk Menganalisis Preferensi Konsumen Dalam Pemilihan Paket Layanan Wedding Organizer Berbasis Website (Studi Kasus: PT. Fifa Management Indonesia) - Melisa Dwi Hestiani; Hadi Zakaria (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
PT. Fifa Management Indonesia is a company that operates in the field of special services in wedding package or wedding organizer services. In the rapidly growing wedding industry, understanding consumer preferences in choosing wedding organizer service packages is crucial for companies to strengthen their position in a competitive market. The problem faced is the absence of an accurate system for analyzing consumer preferences, resulting in a lack of understanding of consumer preferences in choosing wedding organizer service packages to optimize more efficient and accurate wedding organizer service package offerings. To overcome this problem, this research applies the Elimination And Choice Expressing Reality (ELECTRE) method. This method is the right choice in multi-criteria decision analysis that is effective in dealing with the complexity of consumer preferences. Data obtained from consumer surveys is used to build a decision matrix, which is then analyzed using specific software to produce optimal solutions. For this reason, the author implemented an application that allows more structured analysis, so that it can facilitate communication between companies and consumers to more accurately understand consumer preferences. Application development was carried out using the PHP programming language and MySQL database, with the Waterfall system development model. It is hoped that this research can help PT. Fifa Management Indonesia in increasing effectiveness in understanding consumer preferences in choosing wedding organizer service packages that suit their needs. By implementing the Elimination And Choice Expressing Reality (ELECTRE) method and developing structured applications, it is hoped that the decision-making process for offering wedding organizer service packages to consumers will become more measurable, objective and efficient, so as to increase consumer satisfaction and overall company performance.